On the nature and origin of ‘nigate’ - Oguchi, Takashi; Hyugano, Tomoko (Shinrigaku kenkyū, 2002)
This study examined the nature and origin of ‘sense of nigate, ’ which is an awkward and uncomfortable feeling one has toward specific, relatively few others, especially in a interpersonal situation. Study 1 investigated its nature with a questionnaire administered to company employees (200 men and 45 women) and undergraduates (243 men and 205 women). Two factors were found for the sense: troublesomeness and apprehension. It should be noted that apprehension was lower for management than non-management workers. This tendency was due to the worker position, rather than his/her age. In Study 2, self-monitoring scale (Lennox & Wolfe, 1984) was administered to 60 high school students (12 men, 47 women, and one unknown), to investigate the origin of the sense. As predicted, sense of nigate had a negative correlation with the ability to modify self-presentation, and positive one with the sensitivity to expressive behavior in others.